A unified pseudo-Cℓ framework. Issue 3 (16th January 2019) - Alonso, David; Sanchez, Javier; Slosar, Anže; ,
ABSTRACT: The pseudo- C ℓ is an algorithm for estimating the angular power and cross-power spectra that is very fast and in realistic cases also nearly optimal. The algorithm can be extended to deal with contaminant deprojection and E / B purification, and can therefore be applied in a wide variety of scenarios of interest for current and future cosmological observations. This paper presents namaster, a public, validated, accurate, and easy-to-use software package that, for the first time, provides a unified framework to compute angular cross-power spectra of any pair of spin-0 or spin-2 fields, contaminated by an arbitrary number of linear systematics and requiring B - or E -mode purification, both on the sphere or in the flat-sky approximation. We describe the mathematical background of the estimator, including all the features above, and its software implementation in namaster . We construct a validation suite that aims to resemble the types of observations that next-generation large-scale structure and ground-based cosmic microwave background experiments will face, and use it to show that the code is able to recover the input power spectra in the most complex scenarios with no detectable bias. namaster can be found at https://github.com/LSSTDESC/NaMaster, and is provided with comprehensive documentation and a number of code examples.